2007
DOI: 10.1007/s00213-007-0751-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic methadone treatment and repeated withdrawal impair cognition and increase the expression of apoptosis-related proteins in mouse brain

Abstract: Our data suggest that neural apoptotic damage could contribute to impairment of the cognitive abilities of mice observed after chronic methadone administration and withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Animal experiments in mice have revealed that methadone treatment (2.5-10 mg/kg) once daily for three weeks with repeated withdrawals on Saturdays and Sundays has a negative impact on cognitive function, regardless of whether methadone is detectable in brain tissues (5). In addition, neural apoptotic damage caused by chronic methadone administration occurs in mouse brain white matter (6) and correlates with memory dysfunction and depression in former heroin users receiving MMT (7).…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments in mice have revealed that methadone treatment (2.5-10 mg/kg) once daily for three weeks with repeated withdrawals on Saturdays and Sundays has a negative impact on cognitive function, regardless of whether methadone is detectable in brain tissues (5). In addition, neural apoptotic damage caused by chronic methadone administration occurs in mouse brain white matter (6) and correlates with memory dysfunction and depression in former heroin users receiving MMT (7).…”
Section: Introductionmentioning
confidence: 99%
“…There is also some evidence for impaired cognitive function in methadone treatment from the mouse model. Tramullas et al (2007) ascertained impairment of cognitive abilities by chronic methadone in the Morris water maze.…”
Section: Introductionmentioning
confidence: 99%
“…However, administration of β-endorphin facilitated retrieval of a shuttle avoidance task (Izquierdo 1980), and morphine had no effect on the retrieval of inhibitory avoidance (Castellano and McGaugh 1989). Furthermore, Tramullas et al (2007;2008) found impairments on a Morris water maze task after chronic intermittent administration of methadone, but facilitation on a passive avoidance task. Evidently, the effects of acute mu agonists on retrieval appear dependent on the dose and on the nature of the task.…”
Section: Pumps Inmentioning
confidence: 95%